Increases in absenteeism among health care workers in Hong Kong during influenza epidemics, 2004–2009. Issue 1 (December 2015) - Ip, Dennis; Lau, Eric; Tam, Yat; So, Hau; Cowling, Benjamin; Kwok, Henry
Abstract Background Acute respiratory infections (ARI) are a major cause of sickness absenteeism among health care workers (HCWs) and contribute significantly to overall productivity loss particularly during influenza epidemics. The purpose of this study is to quantify the increases in absenteeism during epidemics including the 2009 influenza A(H1N1)pdm09 pandemic. Methods We analysed administrative data to determine patterns of sickness absence among HCWs in Hong Kong from January 2004 through December 2009, and used multivariable linear regression model to estimate the excess all-cause and ARI-related sickness absenteeism rates during influenza epidemics. Results We found that influenza epidemics prior to the 2009 pandemic and during the 2009 pandemic were associated with 8.4 % (95 % CI: 5.6–11.2 %) and 57.7 % (95 % CI: 54.6–60.9 %) increases in overall sickness absence, and 26.5 % (95 % CI: 21.4–31.5 %) and 90.9 % (95 % CI: 85.2–96.6 %) increases in ARI-related sickness absence among HCWs in Hong Kong, respectively. Comparing different staff types, increases in overall absenteeism were highest among medical staff, during seasonal influenza epidemic periods (51.3 %, 95 % CI: 38.9–63.7 %) and the pandemic mitigation period (142.1 %, 95 % CI: 128.0–156.1 %). Conclusions Influenza epidemics were associated with a substantial increase in sickness absence and productivity loss among HCWs in Hong Kong, and there was a much higher rate of absenteeism during the 2009 pandemic. These findings could inform better a more proactive workforce redistribution plans to allow for sufficient surge capacity in annual epidemics, and for pandemic preparedness.